2006
DOI: 10.1021/cm0621390
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution in Metal Oxide/Semiconductor Colloidal Nanocrystal Heterostructures

Abstract: Colloidal nanocrystal heterostructures in which two or more chemically distinct inorganic components are epitaxially fused together provide new opportunities in developing multifunctional building block materials. The ability to synthesize structurally and chemically well-defined nanocrystal heterostructures can provide novel combinations of unique properties arising at the nanometer length scale. Here, we examine the structural evolution of inverse spinel iron oxide/CdS nanocrystal heterostructures with respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 36 publications
2
66
0
Order By: Relevance
“…The calculated interplanar distance was 0.34 nm, which is in a good agreement with the standard data of cubic zinc blende CdS. It is interesting to remark that the (1 1 1) planes of the inverse spinel iron oxide and the (1 1 1) planes of the fcc CdS have a substantial lattice mismatch of approximately 4.4% [3]. Nevertheless, the HRTEM images shown in Figure 3 implied formation of heteroepitaxially grown junction.…”
Section: Characterisation Techniquessupporting
confidence: 84%
See 1 more Smart Citation
“…The calculated interplanar distance was 0.34 nm, which is in a good agreement with the standard data of cubic zinc blende CdS. It is interesting to remark that the (1 1 1) planes of the inverse spinel iron oxide and the (1 1 1) planes of the fcc CdS have a substantial lattice mismatch of approximately 4.4% [3]. Nevertheless, the HRTEM images shown in Figure 3 implied formation of heteroepitaxially grown junction.…”
Section: Characterisation Techniquessupporting
confidence: 84%
“…A possible combination for such a multifunctional nanostructure may be ferric oxide nanoparticles as a magnetically active component for the core and a semiconductor as the photoactive component for the shell. Kwon et al [3] have successfully synthesised Fe 3 O 4 -CdS heterostructure using a high temperature method. In another study by McDaniel and Shim [4], size and growth rate dependent structural characteristics of Fe 3 O 4 -CdS have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to rationalize the formation of peanut-shaped FePt-In 2 O 3 hetero-dimer MHNCs (Wu et al, 2011a), the crystallographic relationships holding between two materials were first investigated on the basis of the coincidence site lattice theory (CSLT) (Randle, 1997;Kwon and Shim, 2005;Kwon et al, 2006; McDaniel and Shim, 2009). In the CSLT approach, starting from the assessment of the relative domain orientations in a MHNC upon analysis of the relevant HRTEM data, the degree of matching between points of the concerned lattices and the frequency at which this correspondence occurs along the relevant heterojunction planes can be studied.…”
Section: Heterogeneous Nucleation Direct Heterogeneous Nucleationmentioning
confidence: 99%
“…When faceted NCs enclosed by relatively large and stable facets with comparable surface atomic structure and/or reactivity are utilized as seeds, growth of numerous domains of the secondary components may occur on the equivalent facets or on the many surface sites (e.g., defects, edges) where nucleation may be kinetically favored and/or interfacial strain may be minimized. These circumstances may lead to heterostructures made of patchy or flower-like architectures, in which multiple satellites of the secondary material are assembled around a single central core that corresponds to one of the starting seeds (Kwon et al, 2006;McDaniel and Shim, 2009;Peng et al, 2011;Zhai et al, 2011;Hou et al, 2012;Lee et al, 2012;Mao et al, 2013;Yu et al, 2015). Depending on the specific case, the use of appropriate surface-binding surfactants (Mao et al, 2013) or judicious adjustment of the reducing conditions (Zhu et al, 2013) have been identified as effective strategies for either accentuating or leveling off the reactivity of the available seed locations, thereby modulating the frequency of heterogeneous nucleation events (Figures 2H-J).…”
Section: Heterogeneous Nucleation Direct Heterogeneous Nucleationmentioning
confidence: 99%
See 1 more Smart Citation